2020
DOI: 10.3171/2020.1.peds19537
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after surgery for catastrophic epilepsy in infants: institutional experience and review of the literature

Abstract: OBJECTIVEUncontrolled epilepsy is associated with serious deleterious effects on the neurological development of infants and has been described as “catastrophic epilepsy.” Recently, there has been increased emphasis on early surgical interventions to preserve or rescue neurodevelopmental outcomes in infants with early intractable epilepsy. The enthusiasm for early treatments is often tempered by concerns regarding the morbidity of neurosurgical procedures in very youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Similar outcomes were reported for temporal lobe surgery in infants (up to 4.5 years of age) 31 . Ye et al reported a 68% Engel I among 38 infants who underwent surgery before 1 year of age 49 . Honda et al reported 66% seizure‐free among 12 infants up to 9 months old undergoing hemispherotomy 34 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar outcomes were reported for temporal lobe surgery in infants (up to 4.5 years of age) 31 . Ye et al reported a 68% Engel I among 38 infants who underwent surgery before 1 year of age 49 . Honda et al reported 66% seizure‐free among 12 infants up to 9 months old undergoing hemispherotomy 34 .…”
Section: Discussionsupporting
confidence: 53%
“…In a survey by Steinbock et al, 56% of infants (1–35 months old) received intra‐ or postoperative blood products 25 . Ye et al reported no need for intraoperative blood product transfusion and no hydrocephalus following 38 surgeries in infants younger than 1 year of age 49 . Gröppel et al compared the safety of epilepsy surgery before 1 year of age (3–9 months) to elder infants (16–32 months) and reported no complications in either age groups 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical findings of affected infants are intractable epilepsy, psychomotor sequelae and contralateral motor deficit 3. Most symptomatic cases are managed via surgical hemispherectomy9 or temporising endovascular embolic hemispherectomy 10. Rarely, some patients may be stable on antiepileptic therapy11 and, more recently, mTOR inhibitors such as rapamycin 12.…”
Section: Discussionmentioning
confidence: 99%
“…Schramm et al reported a mortality rate of 1.0 % in a large retrospective pediatric series while in the adult series of the same center the reported mortality rate was 0 % ( Schramm et al, 2012 ; Althausen et al, 2013 ). Likewise, several recent pediatric series have reported 0 % mortality ( Dorfer et al, 2013b ; Moosa et al, 2013 ; Ye et al, 2020 ). The transformation of the procedure from an extensive resection to a minimal disconnection, the avoidance of cortical vessel coagulation of the pathological hemisphere, and the advances in neuroanesthesia during the last two decades may well explain the minimization of the associated mortality.…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 92%